A Zn(OTf)2 catalyzed Ugi-type reaction of 3-(2-isocyanoethyl)indoles with indole-derived ketimines: rapid access to hexacyclic spiroindolines. Issue 15 (14th June 2018) - Liu, Yun-Lin; Mao, Xiang-Yu; Lin, Xiao-Tong; Chen, Guo-Shu
Abstract : A Zn(OTf)2 catalyzed Ugi-type reaction of 3-(2-isocyanoethyl)indoles and indole-derived ketimines was developed for the synthesis of hexacyclic spiroindolines featuring three stereocenters including two quaternary stereocenters. Abstract : We report a Zn(OTf)2 catalyzed Ugi-type reaction of 3-(2-isocyanoethyl)indoles and indole-derived ketimines to rapidly afford hexacyclic spiroindolines featuring three stereocenters including two quaternary stereocenters in moderate to excellent yields (30–89%) with complete diastereoselectivity. This reaction is highly efficient because two C–C and one C–N bonds as well as two new rings are created under mild reaction conditions in a single step.